THE CONCEPT OF GENDER IN LANGUAGE (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Language is not only a means of communication but also shapes our understanding of the world, reflecting and reinforcing existing social inequalities and stereotypes. This article examines language as a social phenomenon and its relationship with gender norms and stereotypes. It analyzes how language reflects and maintains gender inequalities, as well as how it can be used to change and rethink these norms and stereotypes.